(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A banana heart(Musa acuminate)is a fleshly purple-skinned and tear-shaped flower that grows at the end of a banana fruit cluster. The banana heart is traditionally used in Southeast Asian and Indian cooking and can be eaten raw. Banana heart its chunky flaky texture makes it an ideal substitute for fish. Siomai is the Surapong Filipino term for steamed Chinese dumpling that is usually filled with pork and occasionally with shrimp. For Americans, it can be pronounced as“siumai” (siu mai) or “shumai”(shu mai). In the Mandarin language, it is “shaomai.” The technique used was the survey method, and the instrument used to gather information was a questionnaire. The researchers used the survey method because it is useful in describing the characteristics of a large population gathering the data by asking questions to the people who have the information needed. This research used an experimental research design and sampling random methods. The respondents included 50Grade 12 Home Economics (HE) Strand students and HE teachers. The weighted mean for the students was 3.84, with the verbal interpretation of highly accepted. The weighted mean was 3.99, with the verbal interpretation of highly accepted. The teachers said that they like the taste, aroma, nutritional value, competitiveness, and presentation of the product. The researchers made this product to introduce a new flavor of siomai for the customer to have healthier options in the market. This research will help future researchers in conducting their studies. This research aimed to determine the viability of banana heart siomai and introduce a more nutritious version of siomai to the customers.